2017
DOI: 10.1155/2017/9425864
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte Composition for Distinguishing Corrosion Mechanisms in Steel Alloy Screening

Abstract: The formation and breakdown of passive layers due to pitting corrosion are a major cause of failure of metal structures. The investigation of passivation and pitting corrosion requires two different electrochemical measurements and is therefore a time consuming process. To reduce time in material characterization and to study the interactions of both mechanisms, here, a combined experiment addressing both phenomena is introduced. In the presented electrolyte the different corrosion mechanisms are distinguished… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Characteristic values such as the height and position of the oxidation peaks or the passive current density (i pas ) provide information about the passive layer stability and the corrosion resistance. By adding sodium chloride to the electrolyte, additional characteristic values such as the pitting potential can be determined [29]. The peak heights i peak , the passive current densities i pas derived from the CVs and the corrosion current densities i corr , derived from LSV measurements, of both samples revealed differences in the electrochemical behaviors of the steels (Figure 25b).…”
Section: Results Of Electrochemical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristic values such as the height and position of the oxidation peaks or the passive current density (i pas ) provide information about the passive layer stability and the corrosion resistance. By adding sodium chloride to the electrolyte, additional characteristic values such as the pitting potential can be determined [29]. The peak heights i peak , the passive current densities i pas derived from the CVs and the corrosion current densities i corr , derived from LSV measurements, of both samples revealed differences in the electrochemical behaviors of the steels (Figure 25b).…”
Section: Results Of Electrochemical Characterizationmentioning
confidence: 99%
“…and process parameter can be adjusted to investigate different corrosion phenomena. Changes of the characteristic values of linear sweep voltammetry, cyclic voltammetry and impedance spectroscopy can correlate with changes in the micro structure, like phase composition and grain size, and thus mechanical properties on the different scales [28][29][30]. In addition, when heating the samples with the GKZ heat treatment, two endothermic peaks were measured (carbide formation and austenitizing).…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…According to Babic and Metikos-Hukovic [ 26 ] and Bösing et al [ 36 ], the peaks observed in Figure 5 a,c during anodic sweeping (P.Ox.) are associated with the electroformation of Fe(OH) 2 layers and their oxidation to form FeOOH layers, while the peaks noted during cathodic sweeping (P.Re.)…”
Section: Resultsmentioning
confidence: 91%
“…are associated with a reduction in these products. The Fe(OH) 2 and FeOOH layers form on a pre-existing protective Cr 2 O 3 layer [ 26 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…All potentials in this paper are referred to the Ag/AgCl electrode. The electrochemical measurements, potentiodynamic polarization scans and electrochemical impedance spectroscopy, were done in phosphate buffered saline (PBS) containing 0.2 M NaCl + 0.1 M phosphate buffer solution [17] (pH = 7.5). Before each measurement the working electrodes were wet grinded with SiC grinding paper up to 2000 grid, degreased in ethanol and cleaned in an ultrasonic bath containing deionized water.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%